2015
DOI: 10.3168/jds.2015-9379
|View full text |Cite
|
Sign up to set email alerts
|

Updating the Cornell Net Carbohydrate and Protein System feed library and analyzing model sensitivity to feed inputs

Abstract: The Cornell Net Carbohydrate and Protein System (CNCPS) is a nutritional model that evaluates the environmental and nutritional resources available in an animal production system and enables the formulation of diets that closely match the predicted animal requirements. The model includes a library of approximately 800 different ingredients that provide the platform for describing the chemical composition of the diet to be formulated. Each feed in the feed library was evaluated against data from 2 commercial la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
106
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(139 citation statements)
references
References 43 publications
(47 reference statements)
13
106
1
1
Order By: Relevance
“…The separation of the rumen-fill effect of each fraction (D and I) according to Waldo et al (1972), allows for a combined evaluation of the interaction effects of the passage and digestion kinetics on the fiber filling effect at the rumen compartment (Van Soest, 1994;Vieira et al, 2000a,b). Besides, other important quantitative variables in the feeds can be estimated, such as the energy availability and daily amount of metabolizable protein, which enables the prediction of animal performance based on known dietary inputs (Vieira et al, 2000c;Jardim et al, 2013;Jardim et al, 2015;Higgs et al, 2015). In the present study (Table 4), the average RF(I) was approximately 32% greater than RF(D), a situation that was also observed by Vieira et al (2000b) based on extrusa samples taken from a tropical grassland.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…The separation of the rumen-fill effect of each fraction (D and I) according to Waldo et al (1972), allows for a combined evaluation of the interaction effects of the passage and digestion kinetics on the fiber filling effect at the rumen compartment (Van Soest, 1994;Vieira et al, 2000a,b). Besides, other important quantitative variables in the feeds can be estimated, such as the energy availability and daily amount of metabolizable protein, which enables the prediction of animal performance based on known dietary inputs (Vieira et al, 2000c;Jardim et al, 2013;Jardim et al, 2015;Higgs et al, 2015). In the present study (Table 4), the average RF(I) was approximately 32% greater than RF(D), a situation that was also observed by Vieira et al (2000b) based on extrusa samples taken from a tropical grassland.…”
Section: Discussionsupporting
confidence: 50%
“…Therefore, the variability of this fraction in the pasture is difficult to predict, e.g., Vieira et al (2000a) analyzed esophageal extrusa samples collected from a natural grassland containing U. decumbens and found 11 g kg −1 DM in the dry season and 40 g kg −1 DM in the rainy season. That variability led Higgs et al (2015) to state that in loco evaluation of the protein fractions of the forage resources is the first strategy to predict animal performance more accurately if the feed library does not contain robust estimates of the feed resources available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, microbial-N production was also determined. In order to evaluate the degradation potential of the amino acid sources, nitrogen fractionation [14] was used. The results indicated that F was more rumen degradable than SB as fraction A 2 in this amino acid provider was higher than that in SB.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium sulfite and heat stable alpha amylase were not used in the NDF and ADF assays, and were expressed without residual ash. Nitrogen fractionation was carried out as described by Higgs et al [14]. Briefly, the proteins of SBM and Fortid ® were divided into five fractions, namely A 1 , A 2 B 1 , B 2 and C. The A 1 fraction is made up of ammonia, and calculated by: Ammonia × (SP/100) × (CP/100) (% of CP); where SP is the soluble protein and CP is the crude protein.…”
Section: Chemical Compositionmentioning
confidence: 99%